2016
DOI: 10.15386/cjmed-598
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence of paranasal sinuses anatomical variants in patients with sinusitis using Cone Beam Computer Tomography

Abstract: Background and aimsTo asses, by using the Cone Beam CT (CBCT) reformatted images, the presence of anatomical variants of the sinonasal cavities and to determine the correlation of these variations with the onset of maxillary sinus inflammations.MethodThe study is a retrospective one and consists of the investigation of 130 patients with CBCT imaging, patients that were referred to the Maxillo-Facial Clinic, Radiology Department of the Iuliu Hatieganu University of Medicine and Pharmacy in Cluj-Napoca, for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 8 publications
1
27
1
3
Order By: Relevance
“…6,29,33 Haller cells (Figure 1 b) are ethmoid air cells that extend laterally over the medial aspect of the roof of the maxillary sinus; they may cause narrowing of the infundibulum. 27 In the present study, Haller cells were frequent variants and found in 70.5% of the scans (Figure), but other authors have reported a wide variation in the prevalence rates such as 25%, 1 9.1%, 33 8%, 34 and 33%. 31,35 Onodi cell was found in 44.7% of the scans in the current study.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…6,29,33 Haller cells (Figure 1 b) are ethmoid air cells that extend laterally over the medial aspect of the roof of the maxillary sinus; they may cause narrowing of the infundibulum. 27 In the present study, Haller cells were frequent variants and found in 70.5% of the scans (Figure), but other authors have reported a wide variation in the prevalence rates such as 25%, 1 9.1%, 33 8%, 34 and 33%. 31,35 Onodi cell was found in 44.7% of the scans in the current study.…”
Section: Discussioncontrasting
confidence: 41%
“…In the present study, 57 patients were found with paradoxical middle turbinates (19%) near to a study done in India 18%. 31 Roman et al 1 have found this variant in 8% of their cases, Adeel et al 2 in 14.3% and Kaya et al 6 in 4.3%. The uncinate process (UP) is a structure that has multiple variations between individuals.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The paranasal sinuses include maxillary, ethmoid, frontal and sphenoid sinuses. 1,2 The main functions of paranasal sinuses include lightening of skull, air humidification and voice resonance. [3][4][5] There are various imaging modalities available for the evaluation of the paranasal sinuses.…”
Section: Introductionmentioning
confidence: 99%